"Silent virtuous teachers": anatomical dissection in Taiwan. (16th December 2009) - Lin, Steven C; Hsu, Julia; Fan, Victoria Y
Abstract : Steven C Lin, Julia Hsu, and Victoria Y Fan describe how the dissection course at Tzu Chi College of Medicine in Taiwan has motivated and inspired people to donate their bodies for scientific endeavours, an otherwise culturally avoided gesture in the East